2022
DOI: 10.1075/jslp.21035.dar
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensibility improvements in integrated pronunciation instruction

Abstract: Integration of pronunciation into content courses is appealing because of its potential in helping learners apply their developing pronunciation skills in spontaneous speech. However, the effectiveness of pronunciation instruction (PI) when it is integrated still needs to be demonstrated. This study evaluates whether a group receiving integrated PI (targeting suprasegmentals) improved in controlled and spontaneous speech tasks, compared to a group who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In the context of the acquisition of second language pronunciation, our study backs up the general claim made by various researchers that suprasegmental (e.g. Darcy, Ewert & Lidster, 2012) or rhythmic training including a variety of activities can enhance the learning of prosody in a second language (e.g. on the use of rap music, see Fischler, 2009; on the use of beat gestures, see Gluhareva & Prieto, 2017;Kushch, 2018; on the use of hand-clapping, see Iizuka et al, 2020;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…In the context of the acquisition of second language pronunciation, our study backs up the general claim made by various researchers that suprasegmental (e.g. Darcy, Ewert & Lidster, 2012) or rhythmic training including a variety of activities can enhance the learning of prosody in a second language (e.g. on the use of rap music, see Fischler, 2009; on the use of beat gestures, see Gluhareva & Prieto, 2017;Kushch, 2018; on the use of hand-clapping, see Iizuka et al, 2020;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…In fact, instruction seems beneficial even for learners with fossilized characteristics (Derwing, Munro, & Wiebe, 1997;Derwing et al, 2014), and in short amounts of instruction embedded within communicative classes (Levis & Muller Levis, 2018). Despite these key findings, teachers in different contexts do not necessarily approach pronunciation instruction systematically (Darcy, Ewert, & Lidster, 2012;Foote, et al, 2011;Huensch, 2019;Macdonald, 2002). This is in part due to lack of training in areas such as phonetics, phonology, L2 speech development theory, and pronunciation pedagogy (Couper, 2016(Couper, , 2017Murphy, 2014bMurphy, , 2017, and it has been demonstrated in different studies that investigated what teachers believe, think, and know about pronunciation instruction.…”
Section: Literature Review 1 Pronunciation Teaching and Learningmentioning
confidence: 99%
“…L2 pronunciation research [53][54][55] has demonstrated the superiority of explicit instruction combined with communicative form-focused instruction (FFI) over explicit instruction alone. FFI entails drawing learners' attention to form in communicative contexts, that is, practicing L2 pronunciation while being engaged in contextualized meaning-oriented communicative activities [20].…”
Section: Form-focused Communicative Instructionmentioning
confidence: 99%